Contribuições da biblioteca do Colégio Adventista Paul Bernard ao ensino e ao aprendizado dos alunos de alfabetização no período 2020 a 2021 - Sousa, Evelyn Julia Desiderio Gomes de (Brasil, 2022)
It presents the results of the study developed on the contributions of the College Adventist Paul Bernard Library to the teaching and learning of literacy students from 2020 to 2021. Of an exploratory-descriptive nature, the study aimed to investigate the operational infrastructures of the College Library, to assess their contributions to the literacy process of students. Regarding the methodological procedures, bibliographic, field and documentary research were carried out. The first to select the theoretical contributions that guided the analysis of the information obtained in the collection stage, the second to extract information from the routines of the Library of this College and its pedagogical project and the third to select the technical contributions that discipline the performance of the institutions of the elementary school I and the functioning of school libraries. As for the results of the study, it was found that the infrastructures of the College Paul Bernard Library met the technical standards defined by CFB Resolution n° 220/2020, especially regarding physical space, furniture and equipment, collection, personnel and services.